(3deM GdSMQ ef QhM GdTYQ hQhM GdSMQs - (3CHhYKeGf SYO Hf CMeO Hf EHQGgje Hf djhf GdJLjHj GdCfOdSjs; (3GHf GdLdGHj , eMeO Hf CMeO Hf eMeO GdLdGH GdagQj, CHh YHO Gddg,J (B664 (3g` s ((3CHheOjf Hf CMeO Hf eMeO Hf YHOGdbGOQ GdYHGSj s)
(3ChdgG (B:s
(3hHYO, aEf GdCOH ef CXQa eG JRjf Hg Chdh GdMSH s
(3BNQgG (B:s
(3hPdc HeOjfI GdeQjI MQSgG Gddg JYGdi aj ChGNQ QLH GdaQO ef YGe JSYI hKdGKjf hSHY eFI s
(3fSNI KGfjIs
(3JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGXs
(3hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs